Influence of He and Ar injection on ammonia production in N2/D2 plasma in the medium flux GyM device. (August 2017) - Laguardia, L.; Caniello, R.; Cremona, A.; Gatto, G.; Gervasini, G.; Ghezzi, F.; Granucci, G.; Mellera, V.; Minelli, D.; Negrotti, R.; Pedroni, M.; Realini, M.; et al.
Highlights: LN2 + LIC system is a valid technique to detect ammonia produced during nitrogen seeded D plasma experiments. Ammonia was formed only during plasma phase as demonstrated by QMS. Ammonia conversion decreases whit increasing of the total pressure and increases when the electron temperature increases. He addition reduces ammonia formation. Abstract: Nitrogen used to reduce the power load onto the divertor in tokamak fusion devices (JET, AUG) has the drawback of ammonia formation. Non-negligible quantity of tritiated ammonia could be a serious concern for ITER, since it cannot be reduced through the presently designed fuel cycle loop. In this paper we report a study of the production of ND3 as a function of the electron temperature (Te ) and neutral pressure in a N2 /D2 plasma mixture in the linear machine GyM. The nitrogenized compounds were monitored by Optical Emission Spectroscopy (OES) and Mass Spectrometry (MS). Measurements were performed at different values of Te ranging from 3 eV to 6 eV by varying the microwave power (2.45 GHz, up to 0.6 kW cw) that sustains the plasma, and for different neutral pressure at a constant ratio of nitrogen and deuterium partial pressures. The effect of introduction of He or Ar in the N2 /D2 mixtures has been also investigated. The ND3 produced during plasma experiments has been quantified with a dedicated setup based on an in-line LN2 trap and Liquid Ion Chromatography (LIC). Mass-spectrometry results showed that ND3 is formed only during the plasma phase of the experiment while LIC showed that ammonia production increases with Te and with the total neutral pressure. Optical Emission Spectroscopy confirms the presence of ND species in all the cases studied. The addition of He and Ar in the N2 /D2 plasma, not modifing Te and ne, causes a reduction of ammonia formation, that is negligible in the case of Ar addition, while in the case of He reaches 80%. This suggests that He modifies the physical chemical process occurring at the wall, where the adsorbed He inhibits the reactions leading to ammonia formation at the metallic surface of the vessel. These results confirm the active role of a metallic surface in ammonia production and indicate He injection as a promising solution to limit the formation of the tritiated ammonia in the N seeded plasma of ITER.